The interpolation of cadmium in soils of an urbanized territory of the steppe Dnieper region using geoinformation modeling methods - Gunko, S. O; Tsvetkova, N.M; Neposhivaylenko, N. O (Biosystems diversity, 2018)
We collected data on the content of gross and mobile forms of cadmium in the genetic horizons of the main types of soils of the steppe Dnieper region in anthropogenically contaminated landscapes (for instance, the city of Kamianske). The content and distribution of gross and mobile forms of cadmium are shown laterally and radially. The highest concentration of cadmium content is noted for profiles 1 to 6, in particular for a root-saturated ground horizon (up to 50 cm). For soil horizons located at a depth of 50–150 cm, there is a slight excess (4–6 mg/kg) of the mean (2–4 mg/kg) for all urban systems. Minimal concentrations of gross forms of cadmium are observed along the soil profile of 25–29 (up to 1 mg/kg), but anomalous excesses are noted at intersections of major highways, which is characteristic for all arranged profiles. The distribution of mobile forms of cadmium for each araigned profile usually duplicates the situation of distribution of gross forms of heavy metal content. The ArcGIS Spatial Analyst's software capabilities in assessing the ecological status of the Kamianske soil according to the content of cadmium are demonstrated in the study. The results of interpolation of cadmium concentration (gross and mobile forms) on the territory of the city for the corresponding soil horizons are given. According to the conducted simulation, it has been established that the soils of almost the entire eastern part of the city (east of the soil profile of 1 to 6) are characterized by the content of the gross form of cadmium in the range of 3 to 4 mg/kg, except for the wooded ravine Vodyana, within the territorial boundaries of which the values of 2 to 3 mg/kg are forecast, as well as in the soils of the southern and central parts of the city. The interpolation of the results of measurements of cadmium content indicates that the abnormal zone is gradually decreasing by area, however, it maintains the maximum values for the city's territory.